Mensur Şehnâme tercümesi (III. Cilt, Vr. 451b-482a) (inceleme-metin-dizin-tıpkıbasım) - Tümkor, Şeyma (My University, 2022)
İran’ın millî destanı olan Şehnâme, Firdevsî tarafından kaleme alınmıştır. İran’ın destansı tarihini konu alan bu eser, Fars edebiyatının yanı sıra dünya edebiyatında da önemli bir yere sahiptir. Eser Türk edebiyatını da etkilemiş, edebiyatımızda manzum ve mensur olmak üzere çeşitli Şehnâme çevirileri yapılmıştır. Bu tez çalışması İstanbul Üniversitesi Nadir Eserler Kütüphanesi’nde 6131-6133 demirbaş numarasıyla kayıtlı olan Mensur Şehnâme Tercümesi üzerinedir. Mütercimi belli olmayan eserin istinsahı Derviş Mustafa tarafından 1773 yılında tamamlanmıştır. Eser hem Eski Anadolu Türkçesinin hem de Osmanlı Türkçesinin dil özelliklerini yansıtmaktadır. Çalışma tercümenin üçüncü cildinin 451b-482a varaklarını kapsamaktadır. Çalışma İnceleme, Metin, Dizin ve Tıpkıbasım olmak üzere dört bölümden oluşmaktadır. Girişte Firdevsî, Şehnâme ve Şehnâme’nin Türkçe tercümeleri hakkında bilgi verilmiş, üzerinde çalışılan nüsha tanıtılarak özetlenmiştir. Birinci bölümde metnin yazım ve ses özellikleri metinden örnekler verilerek incelenmiştir. Metin bölümünde tercüme, varak ve satır numaraları belirtilerek çeviri yazıya aktarılmıştır. Dizin bölümünde metinde geçen kelimeler alfabetik olarak sıralanarak metindeki kullanımlarına göre anlamlandırılmıştır. Çalışmanın sonuna nüshanın tıpkıbasımı eklenmiştir.

The Shahnameh, Iran's national epic, was written by Ferdowsi. This work, which is about the epic history of Iran, has an important place in Persian literature as well as world literature. The work has also affected Turkish literature and many translations of Shahnameh have been made both in verse and in prose in our literature. This thesis work is about the translation of Shahnameh in prose which is registered in the Rare Works Library of Istanbul University with the inventory number of 6131-6133. Although the copy of the work was completed by Dervish Mustafa in 1773, there is no information about the translator. The work reflects the linguistic features of both Old Anatolian Turkish and Ottoman Turkish. The study includes the sheets 451b-482a of the third volume of the translation. The study consists of four chapters: Analysis, Text, Index and Facsimile. In the introduction, information is given about Ferdowsi, Shahnameh and Turkish translations of Shahnameh, the features of the copy were evaluated and summarized. In the first part, the orthographic and phonetic features of the text were examined with examples from the text. In the text chapter, the translation was indicated sheet and line numbers and was transcribed. In the index section, the words in the text are listed alphabetically and explained according to the meanings that are used in the text. The facsimile of the copy was added to the end of the study.
Keywords: History and criticism; Tarih ve eleştiri; Turkish literature; Türk edebiyatı; Türk edebiyatı -- Tarih ve eleştiri Turkish literature -- History and criticism